The impact of employee motivation on organization performance: a case of Zimbabwe Power Company (ZPC) (2013-December 2016) - Masudze, Fionah Isheanesu (Midlands State University, 2019)
The study seeks to unravel the factors that affect Zimbabwe Power Company employees’ motivation and the corresponding effect of the identified motivational factors on workers’ performance and overall productivity. The survey revealed that, among the top ten critical factors (teamwork, work based on contract, supervision based on leadership by example and provision of equipment) had great effect on motivation as well as impact on organization performance. More so communication, love and belongingness, opportunity to undertake challenging task, identification with goal and overtime were among the critical factors. The purpose of this paper is to identify the factors that effects employee motivation and examining the relationship between organizational performance and employee motivation. The study also focuses on the practice and observance of the central factors, empowerment and employee recognition for enhancing employee motivation which leads to organizational effectiveness. The organizations should design their rules, policies and organizational structures that give space to the employee to work well and appreciate them on their tasks fulfillment and achievements. This will surely lead to organizational growth.